PERANAN KEPALA SEKOLAH DALAM PELAKSANAAN PENDIDIKAN KARAKTER DI SEKOLAH MENENGAH PERTAMA (SMP) DI KECAMATAN SINDUE - Afriadi, Afriadi (Katalogis, 2017)
This research aims to describe (1) the condition of the character of  students,  (2)  functions, adjustment,  and  the  process undertaken  in  the  implementation of  the principal character education, (3) development of  a  flagship character performed the principal. Methods used is a descriptive with a descriptive qualitative data analysis techniques of interactive models,  Miles  and  Huberman, and  Likert  scale question form  analysis. The population in this study is a entire  principal a number of 5 persons, a number of 118 teachers, and students to a number of people  at 1,041 person in Sindue Sub-district. Sample. The number of samples of the principal  amounts of 5 people using sampling  a number of principal  samples are  saturated,  280  students are divided into 56 school 5 pupils by  school using  random sampling  techniques,  sample teacher as much as 90 people are  divided  into  18  schools  teachers by  school using random sampling techniques. Engineering data retrieval using  descriptive  analysis  and  interview guide scale Likert. The results showed that: first, the character of  the students in junior high se Sindue Sub-district is divided into (1) characters are weak, (2) strong characters , (3) the character of ugly, (4) good characters. Second, the function, and the process of  adjustment, in character education is done in General by the principal, the difference  is  how to encourage  teachers and students in carrying outactivities of character education  in their respective junior high school. Third, the pre-eminent character development done by the head of the junior school is generally done by dissemination to the program the extracurricular activities. The thing that distinguishes is awarding tasks in a community environment is only done by the head of the junior school the country  5  Sindue.